1984
DOI: 10.1210/endo-114-2-391
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Status Versus Chronologic Age as Predictors of Altered Luteinizing Hormone Secretion in the “Aging” Rat*

Abstract: LH release in response to GnRH injected at 1400 h was measured in young (3-4 months), middle-aged (10-11 months), and old (19-20 months) female rats. Data were compared when animals were grouped by chronological age or according to their vaginal smear pattern 3-4 weeks before treatment, i.e. regular 4-day cycles, constant vaginal cornification (CVC), or persistently leukocytic smears (PL). Compared to young, regularly cycling females (injected on vaginal estrus or diestrus II), the amount of LH released by all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…The nature of the alterations observed might be expected to re sult in less than adequate priming of the pituitary by LHRH and therefore could contribute to the diminished serum LH levels measured in MA females here and in other studies. A diminished pituitary response to LHRH has been reported in aging females [6,34,36] and a decrease in the number of pituitary LHRH receptors has been documented in aging male rats [23]. Whether these age-related changes reflect in trinsic deficits at the level of the pituitary or whether they, in fact, result directly from the altered patterns of hypothala mic LHRH secretion or some combination of these factors remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the alterations observed might be expected to re sult in less than adequate priming of the pituitary by LHRH and therefore could contribute to the diminished serum LH levels measured in MA females here and in other studies. A diminished pituitary response to LHRH has been reported in aging females [6,34,36] and a decrease in the number of pituitary LHRH receptors has been documented in aging male rats [23]. Whether these age-related changes reflect in trinsic deficits at the level of the pituitary or whether they, in fact, result directly from the altered patterns of hypothala mic LHRH secretion or some combination of these factors remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In addi tion, recent data support the existence of a hypothalamic factor that acts to antagonize LHRH-stimulated LH release [15]. Moreover, age-related alterations at the pituitary level have been documented in male and female rats [6,23,34,36]. Differences in the ability of the pituitary of MA females to release LH in response to LHRH have been detected in vivo and in vitro [6.…”
mentioning
confidence: 99%
“…Middle-aged animals have been shown to present substantial changes in the regulation of LH compared to young females in the afternoon of proestrus [13,17,30,53]. It is interesting to notice that the pituitary LHRH-R in crease observed on the second day of diestrus in young animals is abolished in middle-aged cycling rats; further more, maximal proestrus values were lower in this experi mental group.…”
Section: Discussionmentioning
confidence: 74%
“…Our results are in agreement and extend previous fin dings of Marian et al [40] reporting a significant reduction in LHRH-R capacity in the pituitary from old CVC ani mals. Such decrease of LHRH binding sites appears to be a consequence of the endocrine status, the CVC condition it self [13,40], Neural aging has also been studied in terms of capacity of the pituitary gonadotroph to respond to direct hypotha lamic stimulation [15]. It sems interesting to notice in young control animals a different response of the pituitary LHRH-R to ES, according to the phase of the estrous cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of the underlying mechanisms have indi cated the possibility that significant changes might be tak ing place at the hypothalamic and/or pituitary level. The response of the pituitary gland to gonadotropin-releasing hormone (GnRH) infused into the vascular system of mid dle-aged rats has been found to be lower than that of young rats [5,6]. Early in vitro studies showed that pituitary glands from middle-aged rats released less LH in response to a prolonged infusion of GnRH [7], In more recent stud ies, we have shown that pituitary tissue from the specific sub-population of middle-aged rats with attenuated LH surges shows a decreased response to pulses of GnRH [8].…”
Section: Introductionmentioning
confidence: 99%